Pelayanan Publik di Desa - Hanif Nurcholis (Asosiasi Ilmuwan Administrasi Negara (ASIAN), 2017)
Village government isn't delivering basic public services: education, health, and social economy. It is just levy tax land, legitimate of letters, and building infrastructure with mutual cooperation as heritage colonial policy, heerendiensten. Base on this problem, the qualitative research conduct in Loireng Village, Sayung Under District, Demak Regency/District, Central Jawa Province. The objective of this research is to analyze why the village government does not deliver basic public services. Data were collected by observation, document study, and interview. Data analyzed with qualitative descriptive. The new public service theory Denhardt and Denhardt used to analyze it. This research found that village government isn’t formal government but state corporatism which not formed to deliver citizen public services.